2007
DOI: 10.1002/hed.20651
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent salivary gland carcinomas treated by surgery with or without intraoperative radiation therapy

Abstract: Background. The optimal treatment for patients with locally recurrent carcinomas of the salivary glands is unclear.Methods. Ninety-nine patients underwent salvage surgery for locally recurrent salivary gland carcinomas. Eighty-one (82%) had previously received radiation. Thirty-seven patients (37%) received intraoperative radiation therapy (IORT) to a median dose of 15 Gy (range, 12-18 Gy) at the time of salvage.Results. The 1-, 3-, and 5-year estimates of local control after salvage surgery were 88%, 75%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Scala et al reported that 1-year in-field control for patients with negative margins was 82% compared to 56% in those with a positive margin (9). At least five other studies also showed that positive margins (more so for gross residual than microscopic residual) at the time of IORT significantly predicted for in-field failure when compared to close or clear margins (2, 11, 13, 18, 19). In addition, doses of IORT of more than 15 Gy were shown to be associated with better LC (10, 12).…”
Section: Role Of Iort In Head and Neck Tumorsmentioning
confidence: 93%
See 4 more Smart Citations
“…Scala et al reported that 1-year in-field control for patients with negative margins was 82% compared to 56% in those with a positive margin (9). At least five other studies also showed that positive margins (more so for gross residual than microscopic residual) at the time of IORT significantly predicted for in-field failure when compared to close or clear margins (2, 11, 13, 18, 19). In addition, doses of IORT of more than 15 Gy were shown to be associated with better LC (10, 12).…”
Section: Role Of Iort In Head and Neck Tumorsmentioning
confidence: 93%
“…The second study included 37 patients with recurrent SGT who received a median dose of 15 Gy IOERT in addition to EBRT (54 Gy) in 15%. LC at 5 years was better with IORT compared to no IORT (82 vs. 60%) and 5-year OS was 34% for the entire sample (2). …”
Section: Role Of Iort In Head and Neck Tumorsmentioning
confidence: 98%
See 3 more Smart Citations